2021
DOI: 10.3390/biology10100961
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Desert Plants for Endophytic and Biostimulant Microbes: A Strategy for Enhancing Agricultural Production in a Hotter, Drier Future

Abstract: Deserts are challenging places for plants to survive in due to low nutrient availability, drought and heat stress, water stress, and herbivory. Endophytes—microbes that colonize and infect plant tissues without causing apparent disease—may contribute to plant success in such harsh environments. Current knowledge of desert plant endophytes is limited, but studies performed so far reveal that they can improve host nutrient acquisition, increase host tolerance to abiotic stresses, and increase host resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 197 publications
(272 reference statements)
0
11
0
Order By: Relevance
“…In sugarcane, endophytic bacteria, including Enterobacter sp. and Klebsiella sp., were found to significantly promote host plant growth by nitrogen fixation (Lin et al, 2015;Taule et al, 2016), which was also reported to assist in stubborn plant growth on barren dunes (Zhang and White, 2021). Jatropha curcas L., a fuel plant that grows on barren sandy soil, contains a rich population of growthpromoting and nitrogen-fixing bacteria (Methylobacterium strain L2-4), which significantly increases host plant growth and seed yield (Madhaiyan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In sugarcane, endophytic bacteria, including Enterobacter sp. and Klebsiella sp., were found to significantly promote host plant growth by nitrogen fixation (Lin et al, 2015;Taule et al, 2016), which was also reported to assist in stubborn plant growth on barren dunes (Zhang and White, 2021). Jatropha curcas L., a fuel plant that grows on barren sandy soil, contains a rich population of growthpromoting and nitrogen-fixing bacteria (Methylobacterium strain L2-4), which significantly increases host plant growth and seed yield (Madhaiyan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, endophytic fungi inhabiting salt-tolerant desert plants have become the object of careful study in recent years. Despite the limited knowledge of microscopic desert plant inhabitants and their active metabolites, the available evidence shows that endophytes have great potential for use in commercial agriculture, significantly as climate change increases the salinity of arable land and the 1068 (2022) 012040 IOP Publishing doi:10.1088/1755-1315/1068/1/012040 2 agricultural industry needs more environmentally friendly alternatives [5]. Endophytic fungi can produce auxins, gibberellins, and cytokinins.…”
Section: Introductionmentioning
confidence: 99%
“…The global temperature increases day by day due to change in climate. Frequent heat waves have had serious impacts on rice production (Zhang and White, 2021). Historical data analysis envisaged that 7-8% of rice yield has been decreased due to raise in temperature to 1 o C (Baker et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Soil has light grey, poor in fertility and less water holding capacity. Therefore, these desert plants develop some physiological mechanisms like CAM (Crassulacean acid metabolism), modi ed leaf and also take the advantage of microbial endophytes to survive in hostile environment (Zhang and White, 2021).…”
Section: Introductionmentioning
confidence: 99%